2018
DOI: 10.1002/ana.25340
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Botulinum Toxin A for Treating Cramps in Diabetic Neuropathy

Abstract: Local BTX-A infiltration is an efficacious and safe procedure for obtaining a sustained amelioration of muscle cramps associated with diabetic neuropathy. Ann Neurol 2018;84:682-690.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…This significant improvement in pain score is comparable to the results of the study conducted in 1997 by Bertolasi et al where they used botulinum toxin to manage cramps in 5 patients with benign cramps -fasciculation syndrome. [16] The study used clinical and neurophysiological variables collected before and after the administration of botulinum toxin to assess its effects. A significant lowering of clinical cramp severity scores and a significant increase in cramp threshold frequencies was noted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This significant improvement in pain score is comparable to the results of the study conducted in 1997 by Bertolasi et al where they used botulinum toxin to manage cramps in 5 patients with benign cramps -fasciculation syndrome. [16] The study used clinical and neurophysiological variables collected before and after the administration of botulinum toxin to assess its effects. A significant lowering of clinical cramp severity scores and a significant increase in cramp threshold frequencies was noted.…”
Section: Discussionmentioning
confidence: 99%
“…Botulinum toxin A (BTX-A) is known to reduce hyperactivity of a muscle by blockade of acetylcholine release at neuromuscular junction thereby leading to muscle relaxation [14,15] This property of botulinum toxin has been used successfully to manage cramps in patients with diabetic neuropathy and patients with benign fasciculation syndrome. [16,17] Our study aims to assess the efficacy of botulinum toxin A (BTX A) in a well-defined cohort of patients with peripheral neuropathy who suffered from cramps due to various etiologies.…”
Section: Introductionmentioning
confidence: 99%
“…Our study assessed the efficacy of BTX-A which has been reported to effectively manage cramps in other conditions including benign fasciculation syndrome and diabetic neuropathy. [33,36,37] The property of relaxing the muscle by preventing acetylcholine release at the neuromuscular junction has been utilized in ALS patients to manage spasticity, sialorrhea and dysphagia. [38,39,40] Table 2 summarizes the different studies that used medications to manage pain as a result of cramps in patients with ALS.…”
Section: Discussionmentioning
confidence: 99%
“…Botulinum toxin A has shown some promise in treating areas of muscle hyperactivity associated with neuropathy. [47].…”
Section: Treatmentmentioning
confidence: 99%